Implementasi Program Hygiene dan Sanitasi dalam Upaya Penurunan Penyakit Infeksi pada Balita untuk Penurunan Prevalensi Stunting di Puskesmas Tirto 2 Kabupaten Pekalongan - Safa Lahalisi; Yuniarti; Dewi Nugraheni RM; Teguh Irawan (Galen: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Stunting is a public health issue influenced by various factors, including hygiene and environmental sanitation conditions. This study aims to analyze the implementation of hygiene and sanitation programs in efforts to reduce infectious diseases in toddlers as a strategic measure to lower the prevalence of stunting in the working area of Tirto 2 Health Center, Pekalongan Regency. This research employed a qualitative approach with a descriptive narrative method, involving in- depth interviews, observations, and documentation with key informants such as health workers, health cadres, community leaders, and mothers of toddlers. The results show that the implementation of hygiene and sanitation programs, including Community-Based Total Sanitation (STBM) and the provision of proper latrines, has been carried out but faces obstacles such as limited funding, low public awareness, poor hygiene habits, and geographic challenges such as tidal flooding. Factors influencing successful implementation include effective communication, availability of resources, policy implementers’ disposition, and bureaucratic structure. The conclusion emphasizes the need for intersectoral approaches and strengthened community participation in sanitation programs to sustainably reduce the rates of infectious diseases and stunting.